A first-principles adsorption study of functionalized carbon, boron nitride, silicon carbon nanotubes with ifosfamide as vehicles for drug delivery: Thermal analysis - Mahboubeh Pishnamazi; Rami M. Alzhrani; Humood Al Shmrany; Sameer Alshehri (Case Studies in Thermal Engineering)
We investigated the adsorption of ifosfamide (IFS) on the outer surface of zigzag (10, 0) carbon nanotubes (CNT), boron nitride nanotubes (BNNT), and silicon carbon nanotubes (SiCNT), using density functional theory (DFT) calculations at the PBE-D3 level in a water solvent phase. Based on zero-point corrected binding energies (Ebin), IFS exhibits chemisorption through its O-head and Cl-head on CNT (−1.05 eV) compared to BNNT (−0.93 eV), characterized by covalent interaction. In contrast, IFS undergoes physisorption via its O-head on SiCNT with binding energy of −0.68 eV as the most stable model this interaction is driven by electrostatic forces. The formation of complexes between the drug and nanotubes is influenced by charge transfer dynamics. Our thermodynamic analysis demonstrates the Gibbs free energy (ΔG) and enthalpy energy (ΔH) for all models are exothermic and spontaneous. The observed decrease in binding energy for BNNT and CNT correlates with changes in their energy gap, dipole moment, and charge transfer upon IFS adsorption. Notably, SiCNT exhibits a different response with a significant energy gap change leading to an increase in dipole moment and charge transfer. These findings suggest that these nanotubes demonstrate promising sensitivity to the presence of IFS and could be explored as potential drug delivery systems for this drug.